Attainment of Functional and Social Independence in Adult Survivors of Pediatric CNS Tumors: A Report From the St Jude Lifetime Cohort Study - Brinkman, Tara M. (J Clin Oncol, 2018)
PURPOSE: Beyond survival, achieving independence is a primary goal for adult survivors of pediatric CNS tumors. However, the prevalence of and risk factors for failure to achieve independence, assessed with multiple concurrent indicators, have not been examined. PATIENTS AND METHODS: Functional and social independence was assessed in 306 survivors (astrocytoma [n = 130], medulloblastoma [n = 77], ependymoma [n = 36], and other [n = 63]; median current age, 25.3 years [range, 18.9 to 53.1 years]; time since diagnosis, 16.8 years [range, 10.6 to 41.8 years]). Six observed indicators were used to identify latent classes of independence, which included employment, living independently, assistance with personal care, assistance with routine needs, obtaining a driver’s license, and marital status. Physical performance impairments were defined as scores < 10th percentile on measures of aerobic capacity, strength, flexibility, balance, mobility, and adaptive function. Multinomial logistic regression estimated odds ratios (ORs) and 95% CIs were calculated for associations of disease/treatment exposures and impairments in physical performance with nonindependence. RESULTS: Three classes of independence were identified as independent (40%), moderately independent (34%), and nonindependent (26%). In multivariable models, craniospinal irradiation (OR, 4.20; 95% CI, 1.69 to 10.44) and younger age at diagnosis (OR, 1.24; 95% CI, 1.14 to 1.35) were associated with risk of nonindependence versus independence. Beyond impaired IQ, limitations in aerobic capacity (OR, 5.47; 95% CI, 1.78 to 16.76), flexibility (OR, 3.66; 95% CI, 1.11 to 12.03), and adaptive physical function (OR, 11.54; 95% CI, 3.57 to 37.27) were associated with nonindependence versus independence. Nonindependent survivors reported reduced physical but not mental health-related quality of life compared with independent survivors. CONCLUSION: Sixty percent of survivors of pediatric CNS tumors do not achieve complete independence as adults. Reduction in intensity of primary therapies and interventions that target physical performance and adaptive deficits may help survivors to achieve greater independence.